Variability of Atlantic Ocean heat transport and its effects on the atmosphere - Dong, B.; Sutton, R. T. (Annals of Geophysics, 2003)
The variability of the Atlantic meridional Ocean Heat Transport (OHT) has been diagnosed from a simulation of a coupled ocean-atmosphere general circulation model, and the mechanisms responsible for this variability have been elucidated. It has been demonstrated that the interannual variability in Atlantic OHT is dominated by windstress-driven Ekman fluctuations. In contrast, the decadal and multidecadal variability is associated with the fluctuations of the Thermohaline Circulation (THC), driven by the fluctuations in deep convection over the Greenland-Iceland-Norwegian (GIN) Sea. The fluctuations of OHT induce Ocean Heat Content (OHC), and Sea Surface Temperature (SST) anomalies over the tropical and subtropical North Atlantic. The SST anomalies, in turn, have an impact on the atmosphere. The lead-lag relationships between the fluctuations of THC-related OHT and those of OHC and SST raise the possibility that a knowledge of OHT fluctuations could be used to predict variations in Atlantic Sea surface temperatures, and perhaps aspects of climate, several years in advance. A comparison of results from a second, independent, coupled model simulation is also presented, and similar conclusions reached.